Determinants of pedestrian mediolateral foot placement in walking on laterally-oscillating structures and their consequences for structural stability - Bocian, Mateusz; Wdowicka, Hanna; Burn, Jeremy F.; Macdonald, John H.G. (Mechanical systems and signal processing, 2025)
An active control of foot placement in the frontal plane is required to maintain balance during walking. It has been previously shown that, for walking on stationary structures, the foot is placed at a mediolateral distance from the body centre of mass (CoM) determined by the CoM mediolateral velocity at the instance of heel strike plus some constant offset. However, it is currently unknown whether the same relationship applies in walking on laterally-oscillating structures and to what extent the structural motion and visual conditions govern the pedestrian stepping behaviour in this case. To this end, six healthy subjects walked on a custom-built wide-belt self-paced treadmill with and without sinusoidal mediolateral treadmill motion. The visual environment was either that of a laboratory, or one of two scenes set in an immersive virtual reality (VR) delivered via a head mounted display. The VR scenes differed with respect to the type and amount of visual reference cues enabling the estimation of self-motion. Multilevel statistical modelling is performed on kinematic data on the behaviour of the walkers. It is shown that the foot placement control law based on the mediolateral velocity of the centre of mass applies, and that the lateral structural motion or lack thereof and visual conditions modulate the step width in different ways. Based on these findings, simulations of the inverted pendulum pedestrian model are conducted revealing the influence of parameters defining the foot placement control law on pedestrian-generated lateral forces governing the amplitudes of lateral structural response. •Pedestrians walking under various ground motion and visual conditions are tested.•Statistical multilevel models are used to analyse the foot placement control law.•That law is then adopted in simulations of the inverted pendulum pedestrian model.•Self-excited forces are quantified in terms of equivalent added damping and mass.•They are found independent of visual conditions, unlike other force components.